Magnetic Fluctuations Associated With Small-Scale Magnetic Holes in the Martian Magnetosheath - Chen, Yangjun; Wu, Mingyu; Xiao, Sudong; Du, Aimin; Wang, Guoqiang; Chen, Yuanqiang; Pan, Zonghao; Zhang, Tielong (Frontiers in Astronomy and Space Sciences, 2022)
Small-scale magnetic holes (MHs) are common magnetic structures with a spatial scale always smaller than one thermal proton gyroradius (ρ_i) in the turbulent planetary magnetosheath. However, the contribution of small-scale MHs in dissipating energy and transporting particles in turbulent plasmas is still unclear. In this work, we investigate the magnetic fluctuations around the small-scale MHs in the Martian magnetosheath, and compute their spectral indices in the kinetic frequency range. Our statistical results show that the spectral index value gradually decreases from the bow shock to the induced magnetosphere boundary at the nightside of Mars. The small-scale MHs have an obvious influence on the spectral indices of the magnetic fluctuations by their high-frequency components. For most events, these MHs lead to an increase of the spectral index in the kinetic range, and such an increase can be very significant in more than 20% of events. Our results indicate that because of the existence of MH, using the spectral index alone as a diagnostic sometimes is not enough convincing during the analysis of turbulence in planetary environments.